VEGETATIVE SYSTEM PATHOGENETIC ROLE IN CHRONIC BRAIN ISCHEMIA, CEREBRAL HEMODYNAMICS DISORDERS AND AUTONOMOUS DYSREGULATION - Stoyanov, O.M.; Vastyanov, R.S.; Myronov, O.O.; Kalashnikov, V.I.; Babienko, V.V.; Hruzevskiy, O.A.; Turchin, M.I. (World of Medicine and Biology, 2022)
The autonomic system plays a leading pathophysiological role in the majority of pathological syndromes development. Its disturbances have an important role in cerebrovascular disorders both formation and clinical manifestation. The purpose of the present study is to assess the state of the autonomic system, cerebral hemodynamics and cerebrovascular reactivity in patients with chronic cerebral ischemia in the stages of compensation and subcompensation. 81 patients with chronic cerebral ischemia were treated and intensively examined to focus on autonomic dysfunctions evaluation and their clinical expression determination. Cephalalgia was the leading syndrome in patients with chronic cerebral ischemia. Autonomic dysfunctions were registered in all examined persons. Sympathetic skin evoked potentials registration showed central nervous system pathological ischemic processes manifestation worsening, sympathetic skin evoked potentials latency increasing, the second phase of sympathetic skin evoked potentials amplitude decreasing that indicated limbic-reticular complex dysfunction, ergotropic processes depletion and the autonomic functions regulation system instability. The ultrasound data confirm that both autonomic system and vasomotor centers dysfunction is the leading mechanism for cerebral ischemia onset and progression, which resulted in cerebral vessels impaired tone and reactivity, neurovasoactive substances accumulatuion, which contributes to the restructuring of the metabolic circuit of autoregulation with a change in the homeostatic range. The data obtained should contribute to chronic cerebral ischemia treatment optimization taking into account the autonomic system individual characteristics of the patients and their cerebral blood flow reactivity.
Keywords: autonomic system; chronic cerebral ischemia; hemodynamic; cerebrovascular reactivity; sympathetic skin evoked potentials